Elastic properties of poly(ethylene glycol) nanomembranes and respective implications - Zhao, Zhiyong; Zharnikov, Michael (Membranes, 2022)
Free-standing poly(ethylene glycol) (PEG) membranes were prepared from amine- and epoxy-terminated four-arm STAR-PEG precursors in a thickness range of 40-320 nm. The membranes feature high stability and an extreme elasticity, as emphasized by the very low values of Young’s modulus, varying from 2.08 MPa to 2.6 MPa over the studied thickness range. The extreme elasticity of the membranes stems from the elastomer-like character of the PEG network, consisting of the STAR-PEG cores interconnected by crosslinked PEG chains. This elasticity is only slightly affected by a moderate reduction in the interconnections at a deviation from the standard 1:1 composition of the precursors. However, both the elasticity and stability of the membranes are strongly deteriorated by a strong distortion of the network imposed by electron irradiation of the membranes. In contrast, exposure of the membranes to ultraviolet (UV) light (254 nm) does not affect their elastic properties, supporting the assumption that the only effect of such treatment is the decomposition of the PEG material with subsequent desorption of the released fragments. An analysis of the data allowed for the exclusion of so called “hot electrons” as a possible mechanism behind the modification of the PEG membranes by UV light.